Computational complexity and implementation aspects of the incremental hash function - Goi, Bok Min; Siddiqi, M. U.; Chuah, Hean Teik (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2003)
This paper gives the computational complexity and practical implementation aspects of a newly introduced incremental hash function called Pair Chaining & Modular Arithmetic Combining Incremental Hash Function (PCIHF). The boundary conditions of the parameters involved in the update process of PCIHF are examined in depth. It is proved that these basic requirements can be fulfilled easily. It is shown that in applications involving more than one update process if the number of blocks to be replaced is no more than 1/4 of the message blocks needed, the PCIHF is more efficient than standard SHA-1. Finally, it is observed that the computational complexity of combining operation is also important to ensure the practicability of PCIHF.